Multifunctional Carbon Nanohorn Complexes for Cancer Treatment. Issue 1 (15th October 2014) - Chechetka, Svetlana A.; Pichon, Benoit; Zhang, Minfang; Yudasaka, Masako; Bégin‐Colin, Sylvie; Bianco, Alberto; Miyako, Eijiro
Abstract Multifunctional carbon nanohorn (CNH) complexes were synthesized using oxidized CNH, magnetite (MAG) nanoparticles, and polyethyleneimine (PEI). The ferromagnetic MAG nanoparticles were loaded onto CNH (MAG‐CNH) using iron(II) acetate and subsequent heat treatment. Chemical functionalization of the MAG‐CNH complexes with PEI improved their water‐dispersibility and allowed further conjugation with a fluorophore. The application of an external magnetic field significantly intensified the targeted vectorization of CNH complexes into human cervical cancer (HeLa) cells. Following cell uptake, laser irradiation of the cells showed a significant enhancement in the photothermal effects of CNHs leading to cell death. We have confirmed that the photothermal properties and ferromagnetic characteristics of CNH complexes show efficient cell elimination. The present study is an essential step toward the development of an innovative cancer therapy and a highly sensitive detection of cancer cells at the single‐cell level.